INTERNATIONAL Innovative recruitment and clinical orientation programme to manage NHS junior doctor shortfall: A district hospital experience. Issue 2 (2020) - Quadery, Syed Rehan; Roodbari, Hamid; Pardeshi, Pradeep; Shah, Dilip; Ahmed, Hira; Jain, Seema; Saridis, Jason; Rahman, Shakil; Ratnasingam, Nithiyananthan; Ebdon, Caroline; Bogle, Richard; Marsh, James; et al.
No abstract available